The Relationship between Creative Leadership of School Administrators and School Effectiveness in Secondary Education Areas under the Chachoengsao Provincial Education Office - ภัทรเชื้อหอม, ปิยะวัฒน์; แก้วมงคล, ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were 1) to study the creative leadership of school administrators under the Secondary Educational Service Area Office Chachoengsao, 2) to examine school effectiveness under the Secondary Educational Service Area Office Chachoengsao, 3) to investigate the relationship between the administrators' creative leadership and school effectiveness within the same jurisdiction. The research sample consisted of 298 participants, including school administrators and teachers, determined by using the Krejcie and Morgan table. The research instrument was a 5-point Likert scale questionnaire with an Index of Item-Objective Congruence (IOC) ranging from .60 to 1 and a reliability coefficient of .988. Data were analyzed using frequency, percentage, mean, standard deviation, and Pearson’s product-moment correlation coefficient.          The findings of this research indicate that 1) the creative leadership of school administrators, both overall and in each individual dimension, is at a high level, with creativity yielding the highest mean, followed by imagination, while flexibility represents the lowest mean, 2) school effectiveness, both overall and in each dimension, is also at a high level, with the highest mean found in the ability to adapt and develop the school, followed by the ability to develop students' positive attitudes, while the lowest mean is the ability to solve internal problems and 3) the relationship between administrators' creative leadership and school effectiveness shows a statistically significant positive correlation at the .01 level of significance. Specifically, the imagination dimension is highly correlated with effectiveness. When considering individual dimensions of school effectiveness, the ability to solve internal problems shows the highest correlation, reflecting that systematic problem management through initiative is a vital factor for sustainable institutional success. Consequently, administrators should enhance their management flexibility, communicate a clear vision to establish shared goals, and support teachers in utilizing educational technology and active learning innovations to elevate student academic achievement.